Pollen and seed morphology of rhinacanthus nees and hypoestes Sol. ex R. Br. (Acanthaceae) of Yemen - Anisa S. Al-Hakimi; Haja Maideen; Latiff, A. (Universiti Kebangsaan Malaysia, 2015)
Pollens and seeds of Hypoestes and Rhinacanthus collected from different field localities in Taiz and Soqotra Island, Yemen were investigated by using light and scanning electron microscopes. Pollen grains of Hypoestes were prolate in equatorial view, lobate trigonal to lobate circular in polar view whereas those of Rhinacanthus were subspheroidal and rounded trigonal in polar view. The aperture was tricolporate and exine ornamentation was coarsely reticulate for all species in the two genera. Scanning electron microscopy and morphological observations showed that mature dry seeds of Hypoestes and Rhinacanthus have various sizes and shapes, the surface ornamentations observed were reticulate to cristate, an addition to the tuberculum and papillae. The three Hypoestes species differ in the seed structure which are useful for identification and their high structural diversity provides an important taxonomic value for species differentiation.